ANALISIS FATWA MUI NO.13 TAHUN 2019 TENTANG TRANSPLANTASI ORGAN DAN JARINGAN TUBUH DARI ORANG HIDUP UNTUK ORANG LAIN - Rizkiyah, Lujeng (TAHKIM, 2024)
Organ transplantation has become one of the most meaningful solutions in modern medicine. The issue of organ transplantation has given rise to new problems, so it has become one of the most sensitive debates in the medical and religious worlds. The increasing number of patients requiring transplants, organ rejection, post-transplant complications, and the risks that may arise from transplantation have raised questions about the legal and ethical ethics of using this technology. On the other hand, the current development of science and technology in the medical field also triggers various kinds of legal problems, where it is required to be more flexible and applicable in its implementation, not being shackled into a rigid legal system. The ijtihad method used is the istislahi method using the Manhaji approach. The results of this ijtihad confirm that a person may not give or sell organs and/or body tissues to other people because the organs are not proprietary (haqqul milki) for that reason, taking and transplanting organs without any reason justified by syar'i is unlawful.